Scientific substantiation of the medical-sanitary regulations in the soil of modern persistent pesticides - representatives of different chemical classes - Korshun, M.M.; Martіianova Yu.V.; Korshun, O.M. (Environment & Health, 2024)
The aim: scientific substantiation of the medical-sanitary regulations is the maximum permissible concentration in soil of modern persistent pesticides: amicarbazone from the class of triazolones, bicyclopyrone from the class of triketones and pydiflumetofen from the class of pyrazolecarboxamides. Materials and methods. Three stages of research were carried out: mathematical modeling of amicarbazone, bicyclopyrone and pydiflumetofen migration from soil to adjacent environments; laboratory hygienic experiment to examine studied substances behavior in systems «soil – plants», «soil - atmospheric air» and substantiation of their threshold concentrations in soil according to the translocation, air-migration and water-migration indicators of harmfulness; impact study of amicarbazone, bicyclopyrone and pydiflumetofen on the nitrifying activity of leached chernozem and setting their threshold concentrations according to the general sanitary indicator of harmfulness. Results. It was experimentally established that the threshold concentrations in soil according to the water-migration indicator of harmfulness are the concentrations of amicarbazone, bicyclopyrone and pydiflumetofen of 0.02 mg/kg, 0.01 mg/kg, and 0.06 mg/kg, respectively. The calculated threshold concentrations of amicarbazone (0.05 mg/kg), bicyclopyrone (0.02 mg/kg) and pydiflumetofen (0.05 mg/kg), which were obtained by mathematical modeling, turned out to be very close to experimentally determined ones, which proves a rather high prognostic ability of the applied calculation method. The threshold concentration in soil of amicarbazone, bicyclopyrone and pydiflumetofen according to the water-migration indicator of harmfulness turned out to be the lowest compared to the threshold concentrations according to the translocation (0.2 mg/kg, 0.25 mg/kg and 0.12 mg/kg, respectively), air-migration (0.05 mg/kg, 1.0 mg/kg and 1.2 mg/kg, respectively) and general sanitary (0.2 mg/kg, 0.05 mg/kg and in the range 0.12-0.6 mg/kg, respectively) indicators of harmfulness. Therefore, the leading link of studied substance migration in the environment is the «soil – groundwater» system. Conclusions. The MPC of amicarbazone, bicyclopyrone and pydiflumetofen in soil is scientifically justified at the level of 0.02 mg/kg, 0.01 mg/kg and 0.06 mg/kg, respectively, according to the limiting water-migration indicator of harmfulness. Based on the studied substances in the recommended consumption rates and frequency of treatments the usage of plant protection products in the cultivation of agricultural crops will not lead to dangerous to human health contamination of groundwater, agricultural raw materials and atmospheric air, it will not cause a violation of the processes of self-cleaning of soil from nitrogen-containing organic substances in real soil-climatic conditions in Ukraine.